The sub-fossil diatom distribution in the Beibu Gulf (northwest South China Sea) and related environmental interpretation - Zhang, Jinpeng; Witkowski, Andrzej; Tomczak, Michał; Li, Chao; McCartney, Kevin; Xia, Zhen (PeerJ, 2022)
Located in northwestern South China Sea (SCS), the Beibu Gulf constitutes an environmentally sensitive region shaped by land-ocean-atmosphere interactions in Asia between the western Pacific and eastern Indian Oceans. This study aims to provide a comprehensive view of the sub-fossil diatom biogeography, distribution pattern and oceanographic environmental controls with support of multivariate methods based on Beibu Gulf core-top samples. Cluster analysis of diatom assemblages divides the distribution pattern into four subclusters. Sea surface salinity (SSS), temperature (SST), trophic state (chlorophyll a concentration in this study) and water depth constrain the diatom distribution pattern through canonical redundancy analysis although only partly support an interpretation of the relationship between these various variables. Chlorophyll a has a strong correlation to diatom distribution, and responds to Paralia sulcata occurrence, while SSS and SST also have significant influence and indicate warm water invasion from the open SCS. Water depth is a subordinate factor in terms of Beibu Gulf diatom distribution. The ca. 25 m water-depth marks the upper extent of Paralia sulcata dominance in the northern Beibu Gulf. A strong mixing area with a complex diatom distribution exists below this water depth in the middle of Beibu Gulf. Coastal currents from north of SCS invade Beibu Gulf through Qiongzhou Strait and south of Hainan Island, as recorded by higher percentages of Paralia sulcata and Cyclotella striata at these sites. Our results provide a selection of evaluation method for a marine ecological red-line definition for sustainable development. This study highlights the perspective relationships between the spatial distribution of sub-fossil diatom assemblages in surface sediments and oceanographic variables, which could serve as a model for paleoenvironmental and paleoclimatic reconstruction in future marginal sea geoscience research for the Beibu Gulf, northwestern SCS.
Keywords: Diatoms; South China Sea; Oceanographic variables; Paleoceanography; Paleoenvironmental proxies; Multivariate analyses